Agrikutural System In Jorong Koto Tinggi, Baso District, Agam Regency To Support The Achievement Of SDG 2 (Zero Hunger) From An Islamic Economic Perspective - Yolanda, Adisti; Angraini, Dewi Manda; Devy, Tartila; Isriani, Rahmi (Al-Sharf: Jurnal Ekonomi Islam, 2025)
This study analyzes the agricultural system in Jorong Koto Tinggi, Baso District, Agam Regency, in relation to the achievement of Sustainable Development Goal (SDG) 2 “Zero Hunger” from the perspective of Islamic economics. Despite abundant natural resources, most farmers still rely on traditional methods with low productivity, constrained by limited capital, low adoption of technology, limited understanding of sustainable agriculture, as well as the impacts of climate change and commodity price fluctuations. This research employed a descriptive qualitative method through observation, in-depth interviews, and documentation, with data analyzed inductively using reduction, presentation, and conclusion drawing. The findings reveal that agricultural transformation is occurring gradually; some farmers have begun to adopt modern technologies such as hand tractors, rice transplanters, and mini combine harvesters that improve efficiency and productivity, while the majority still depend on manual tools. The main obstacles include limited capital, lack of technical training, inadequate irrigation infrastructure, and resistance to change. From the perspective of Islamic economics, agricultural management should be based on the principles of sustainability (istidamah), public interest (maslahah), and distributive justice to achieve societal welfare (falah).